Relationship between Prescription Services and Patient Satisfaction Level at the Outpatient Installation of X Hospital, South Tangerang City - Novitri, Suci Ahda; Sholehah, Alsyah; Yaenap, Siti; Shavira, Rurynta Ferly (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Prescription service is one of the pharmaceutical services that aims to improve the quality of life of patients. Good service will increase patient satisfaction so that it will affect the quality of life of patients. Patient satisfaction can be assessed by measuring elements of responsiveness, assurance, tangible, empathy, and reliability. The purpose of this study was to determine the relationship between prescription services (waiting time) and the level of patient satisfaction at the South Tangerang City X Hospital. This study was an observational quantitative study with a cross sectional approach using a survey. The number of samples used was 382 respondents through purposive sampling method. The data obtained were analyzed by univariate and bivariate analysis using SPSS version 22. The results showed that the level of patient satisfaction with the elements of responsiveness was 76.65%, assurance was 76.64%, tangibles was 75.28%, empathy was 76.60%, and reliability was 76.21%. Based on the results of the analysis using chi-square, there is a relationship between prescription services and the level of patient satisfaction at the South Tangerang City X Hospital with a p value of 0.000 (p-value <0.05). This study can be concluded that there is a significant relationship between prescription services (waiting time) and the level of patient satisfaction in the outpatient installation of South Tangerang City X Hospital.